Local capital markets for environmental infrastructure : prospects in China, Kazakhstan, Russia and Ukraine - Organisation for Economic Co-operation and Development (Environmental finance, 2006)
Executive summary (s. 9-15).
Keywords: ympäristönsuojelu : Kazakstan; ympäristönsuojelu : Kiina; ympäristönsuojelu : Ukraina; ympäristönsuojelu : Venäjän federaatio; investoinnit; rahoitus